Floral Nectaries, Nectar Production Dynamics and Chemical Composition in Six Ipomoea Species (Convolvulaceae) in Relation to Pollinators - GALETTO, LEONARDO (Ann Bot, 2004)
• Background and Aims Floral nectaries and nectar features were compared between six Argentinian Ipomoea species with differences in their pollinator guilds: I. alba, I. rubriflora, I. cairica, I. hieronymi var. hieronymi, I. indica, and I. purpurea. • Methods Pollinators were recorded in natural populations. The morpho-anatomical study was carried out through scanning electron and light microscopy. Nectar sugars were identified via gas chromatography. Nectar production and the effect of its removal on total nectar sugar amount were determined by using sets of bagged flowers. • Key Results Hymenopterans were visitors of most species, while hummingbirds visited I. rubriflora and sphingids I. alba. All the species had a vascularized discoidal nectary surrounding the ovary base with numerous open stomata with a species-specific distribution. All nectar samples contained amino acids and sugars. Most species had sucrose-dominant nectars. Flowers lasted a few hours. Mean nectar sugar concentration throughout the lifetime of the flower ranged from 34·28 to 39·42 %, except for I. cairica (49·25 %) and I. rubriflora (25·18 %). Ipomoea alba had the highest nectar volume secreted per flower (50·12 µL), while in the other taxa it ranged from 2·42 to 12·00 µL. Nectar secretion began as soon as the flowers opened and lasted for a few hours (in I. purpurea, I. rubriflora) or it was continuous during the lifetime of the flower (in the remaining species). There was an increase of total sugar production after removals in I. cairica, I. indica and I. purpurea, whereas in I. alba and I. rubriflora removals had no effect, and in I. hieronymi there was a decrease in total sugar production. • Conclusions The chemical composition, production dynamics and removal effects of nectar could not be related to the pollinator guild of these species. Flower length was correlated with nectary size and total volume of nectar secreted, suggesting that structural constraints may play a major role in the determination of nectar traits of these species.